PENULISAN LAPORAN HASIL PENELITIAN: REKONSTRUKSI LITERASI DALAM PENJAMIN MUTU PENDIDIKAN - Zikriyanto, Wahyu; Hayadi, B.Herawan; Oktalia, Huda; Nurlena, Elin; Hisaanah, Khauranina; Apriyudin, Apriyudin (STAI Darul Qalam Tangerang, 2026)
Educational quality assurance is frequently ensnared in administrative formalities that overlook the substantive depth of literacy in research reporting, causing its core essence to be largely neglected. This study aims to formulate and reconstruct the role of literacy as a strategic instrument for educational quality assurance, transcending its conventional definition as a mere basic reading-and-writing skill. Employing a descriptive qualitative method with a literature review and participant observation approach, the research reveals that precision and accuracy in research reporting significantly impact the efficiency of institutional policymaking. This reconstruction proves that strengthening narrative and data literacy can transform formal reports into strategic roadmaps for quality enhancement. The study concludes that the standardization of evidence-based reporting is an absolute prerequisite for ensuring sustainable quality within educational institutions.